Non‐anaplastic peripheral T‐cell lymphoma in children and adolescents – a retrospective analysis of the NHL‐BFM study group. (14th November 2014) - Kontny, Udo; Oschlies, Ilske; Woessmann, Willi; Burkhardt, Birgit; Lisfeld, Jasmin; Salzburg, Janina; Janda, Ales; Attarbaschi, Andishe; Niggli, Felix; Zimmermann, Martin; Reiter, Alfred; Klapper, Wolfram
Summary Mature (peripheral) T‐cell lymphoma (PTCL) other than anaplastic large cell lymphoma is a heterogeneous group of diseases and exceedingly rare in children and adolescents. Survival rates range between 46% and 85%. This study reports the disease characteristics, treatment and outcome of all patients with the diagnosis of mature TCL registered in the Berlin‐Frankfurt‐Munster non‐Hodgkin lymphoma database between 1986 and 2012. All diagnoses were centrally reviewed and revised by clinico‐pathological correlation according to the criteria of the current World Health Organization classification. Of the 69 patients originally registered as having PTCL, the diagnosis was confirmed in 38 of them. Most patients were treated with an anaplastic large cell lymphoma (ALCL)‐like therapy regimen. Patients with PTCL‐not otherwise specified comprised the largest group and showed a 5‐year event‐free survival rate of 61 ± 11%. Patients suffering from Natural Killer/T‐cell‐ and hepatosplenic TCL had the poorest outcome. Our results suggest that the outcomes of children with mature TCL other than ALCL depend on the subtype and are worse than in all other paediatric lymphomas. The clinical experience presented in this largest study on paediatric mature TCL may serve as basis for future collaborative international prospective clinical trials.